The importance of hospital hyperglycemia (not exclusive of diabetes) - Russo, María P.; Grande Ratti, María F. (Revista del Hospital Italiano de Buenos Aires, 2022)
As a result of this publication, we review the relationship between financial sustainability and excellence in hospital care. Quality is framed in five fundamental elements: professional excellence, efficient use of resources, minimum risk for the patient, high degree of satisfaction, final impact on health.
Keywords: hospital hyperglycemia; hospital mortality; stress hyperglycemia; epidemiology